Four new alien species on the coasts of Greece (Eastern Mediterranean) - SIMBOURA, N.; KURT SAHIN, G.; PANAGOULIA, A.; KATSIARAS, N. (Mediterranean Marine Science, 2010)
This study reports four alien polychaete species new to the marine fauna of Greece. These species are -Pseudopolydora paucibranchiata (family Spionidae),Paraprionospio coora (family Spionidae), Marphysa disjuncta (family Eunicidae), and Chaetozone corona(family Cirratulidae). Another species of Chaetozone, though not an alien one, Chaetozone gibber is reported here from Greek waters. All of them have been currently reported from the coasts of Turkey (Aegean or Levantine Seas). Pseudopolydorapaucibranchiata and Marphysa disjuncta, probably introduced to the region through ballast waters, seem to have been well established in the Mediterranean Sea. Chaetozone corona and Paraprionospio coorawere considered to be cryptogenic. Pseudolydora paucibranchiata was found in great densities in a very disturbed site, confirming the opportunistic character of this species. Chaetozone corona and Chaetozonegibber showed a wider distribution pattern, though their abundance increased in disturbed sites.Marphysa disjuncta was found in disturbed as well as in undisturbed sites along the coasts of Greece.Paraprionospio coora shows a distribution pattern indicating an opportunistic character. These new findings increase the number of polychaete species from the Hellenic Seas to 777 species.